RIGHT TO HEALTH: A STUDY OF THE CHALLENGES FACED IN HEMATOPOIETIC STEM CELL TRANSPLANTATION - Lima, Daniela Kedna Ferreira; Gonçalves, Carla Agda (Seven Editora, 2025)
This article has as its object the challenges faced by SUS users in accessing Hematopoietic Stem Cell Transplantation HSCT in the interface with the social issue. The theoretical concepts researched were: Social Issue, Health Policy and Access. Dialectical historical materialism was adopted as a method, and as for the methodological path, it is a qualitative research, using some quantitative data; covering bibliographic research – about the conceptual categories; Documentary research (in Laws, decrees, among others); and the Field Research, with SUS users who underwent HSCT as participants. The inferences of this study indicate the challenges experienced by the participants in the search for the right to access health in an integral way in its interface with the social issue. In this sense, the construction of public health policies must be based on the reality and needs of the subjects who use it, built from processes of struggles and mobilizations that reiterate the forms of collective confrontation expressed in the social issue, having as a guiding thread the realization of the rights to health.DOI: https://doi.org/10.56238/sevened2024.037-171